The Right to a Fair Trial: Comparative Analysis of International Human Rights Standards - Arief Fahmi Lubis (The Easta Journal Law and Human Rights, 2023)
This research paper presents a comparative analysis of the right to a fair trial in Indonesia and Brazil, focusing on the international human rights standards applicable in both countries. The study examines the legal frameworks, case studies, and challenges associated with fair trial rights in each country. Through a comprehensive review of literature and analysis of relevant legal provisions, the research highlights the issues of presumption of innocence, access to legal representation, impartiality of the judiciary, and the protection of vulnerable groups. The findings contribute to a better understanding of the practical implementation of fair trial rights and provide insights into areas that require attention and improvement. The research concludes by emphasizing the importance of aligning domestic laws and practices with international human rights standards to ensure comprehensive protection of fair trial rights in Indonesia and Brazil.